Peritoneal De-differentiated Liposarcoma: A Rare Case Report - Hardas, Gauri Vinod; Lad, Lalit; Bora, Harshwardhan; Prasad, Saurabh (Annals of Pathology and Laboratory Medicine, 2023)
Peritoneal de-differentiated liposarcoma is a rare malignancy with a poor prognosis. Our patient, 67 years/Male presented with complaints of constipation & distension of abdomen for one month. Initially based on histology, diagnosis of Gastrointestinal Stromal Tumor (GIST) was thought. On PET scan, he had multiple peritoneal deposits & serosal deposits along recto-sigmoid colon and ileal loop which on immunohistochemistry (IHC) proved to be de-differentiated liposarcoma. The patient was given chemotherapy. Patient responded well to treatment. Such peritoneal tumors pose a challenge to the pathologist as only morphology is not of much help & IHC becomes necessity.